Substitution of corn and soybean oil by cassava meal and African palm tree oil in diets of laying hens - Zacar?as, J. B.; Valdivi?, Manuel; Bicudo, S. J. (Cuban Journal of Agricultural Science, 2012)
Fourty-two White Leghorns laying hens, from the commercial Cuban hybrid L-33, were used for eight weeks during the laying peak (36 to 43 weeks of age), to assess the substitution of corn by cassava root meal (Manihot esculenta Crantz) and the crude soybean oil by crude oil of African palm tree (Elaeis guineensis J.) in the diets of laying hens. Analysis of variance was conducted, according to simple classification design, with three treatments and 14 repetitions (a cage with a hen). The treatments consisted of three diets (1- corn meal + soybean oil; 2- 25 % cassava meal + African palm tree oil; 3- 53 % cassava meal + African palm tree oil), with 15.71 % CP; 3.83 % Ca and 0.36 % P available. The viability was of 100 % in all treatments. No differences were found for laying (92.21, 92.09 and 91.59 %), which surpassed the potential of this hybrid during the laying peak (90 %), conversion (118g feedstuff/egg in the three treatments), egg mass produced (3066, 3114 and 3071 g/bird) and mass conversion (1.99, 1.95 y 1.98 feed consumed/egg mass). The pigmentation of the egg yolk was reduced as the level of cassava meal increased in the diets (6, 4 and 3 at Roche?s scale), as well as the cost of the feed consumed in 56 d per hen (2.56, 2.15 and 1.83 USD/bird). The possibility of substituting, totally, corn meal by that of cassava and soybean oil by that of the African palm tree in the diets of laying hens during the laying peak was determined, with positive economic effect and without damaging the productive performance of birds. Key words: cassava, African palm tree, laying hens.